Developments in 4th generation district heating - Østergaard, Poul Alberg; Lund, Henrik; Mathiesen, Brian Vad (International Journal of Sustainable Energy Planning and Management, 2019)
This editorial introduces the 20th volume of the International Journal of Sustainable Energy Planning and Management. Papers included are all from the conference on 4th generation District heating and Smart Energy Systems, Aalborg, 2017, treating the control of heat systems, technical and non-technical barriers to low-temperature district heating. Temperature levels are also key-parameters in an investigation of heat pumps and heat sources for heat pumps in Tallinn. In parallel to apps focusing on electricity systems, an app focusing on heat systems is presented.